THE APPLICATION OF BUDDHIST VALUES IN CONTEMPORARY EDUCATION IN THE ERA OF DIGITALIZATION - Annisa Ghina Istighfarany; Nina Yudha Aryanti; Andy Corry Wardhani (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Education should be an effective tool to shape individuals capable of developing civilization. Education is defined as a conscious and planned effort to create a learning environment and learning process so that students can actively develop their potential, including spiritual strength, self-control, personality, intelligence, good morals, and skills needed for themselves and society (SISDIKNAS Law No. 20 of 2003). In Buddhism, education is seen as a process rooted in practice (sikkha), where individuals learn, practice, study, develop, and achieve enlightenment. This includes moral discipline (síla), concentration (samadhi), and knowledge or wisdom (pañña). Education in the context of Buddhism is an ongoing effort to improve oneself and become a wise human being. Buddhism, as a religion and philosophy rooted in the teachings of Siddhartha Gautama or Buddha, carries a number of values that can be integrated in the context of contemporary education, namely Compassion (Metta), Wisdom (Panna), Simplicity (Apicchat), Empathy (Karuna). The method used is a descriptive qualitative approach through in-depth interviews with research participants consisting of various stakeholders in the educational environment including schools that have implemented Buddhist values.  By understanding the concept of Buddhism, ethics, implementation methods, and relevance through this approach, this research can provide a strong basis to explore the impact of implementing Buddhist values in contemporary education and identify potential improvements in the education system. It is important to understand the relevance of Buddhism in the complex contemporary educational environment. How Buddhist values can contribute to the formation of wiser, ethical and harmonious individuals in the modern educational context. In this regard, Buddhism can provide a perspective that helps students cope with challenges more calmly and empathetically.